Visual Cultures of Africa - Kidenda, Mary Clare; Kriel, Lize; Wagner, Ernst (Waxmann Verlag, 2022)
The voices in this book offer a multi-perspectival approach to Africa, focusing on the skills and the knowledge underpinning visual cultural expressions ranging from Akan symbolism to embodied performances by dancers and storytellers, even re-designed models of Western cars. Educators, designers, artists, critics, curators, and custodians based both in Africa and in Europe are configuring spaces for public, private, institutional as well as digital conversation - whether through pottery or portraiture, furniture or film, shoes or selfies, buildings or books. Readers are encouraged to question how African visual cultures are both 'in' and 'of'; identifying and confrontational; post- and decolonial; preserved and practised; old and new; borrowed and authentic; composite and complete; rooted and soaring. Disciplines being engaged include visual culture studies, media studies, performance studies, orature, literature, art and design - as well as their histories. The editors Mary Clare Kidenda, Lize Kriel and Ernst Wagner represent three nodes in the Exploring Visual Cultures north-south collaborative network: The Technical University of Kenya, the University of Pretoria in South Africa and Munich Academy of Fine Arts in Germany.